Esther the wonder pig : changing the world one heart at a time - Jenkins, Steve, 1982-; Walter, Derek, 1981-; Crane, Caprice (Grand Central Publishing, 2016)
In the summer of 2012, Steve Jenkins was contacted by an old friend about adopting a micro piglet. Though he knew his partner Derek wouldn't be enthusiastic, he agreed to take the adorable little pig anyway, thinking he could care for her himself. Little did he know, that decision would change his and Derek's lives forever. It turned out there was nothing "micro" about Esther, and Steve and Derek had actually signed on to raise a full-sized commercial pig. Within three years, Tiny Esther grew to a whopping 600 pounds. After some real growing pains and a lot of pig-sized messes, it became clear that Esther needed much more space, so Steve and Derek made another life-changing decision: they bought a farm and opened the Happily Ever Esther Farm Sanctuary, where they could care for Esther and other animals in need.